Parakinesia brachialis oscitans during thrombolytic therapy - Zorzetto, Francis Paciornik (BMJ Publishing Group, 2013)
The authors describe a case report of a patient with parakinesia brachialis oscitans, which occurred during thrombolytic therapy, in a patient with left-middle cerebral artery occlusion.